Molecular Cloning and Characterization of Two Genes for the Biotin Carboxylase and Carboxyltransferase Subunits of Acetyl Coenzyme A Carboxylase in Myxococcus xanthus - Kimura, Yoshio (American Society for Microbiology, 2000)
We have cloned a DNA fragment from a genomic library of Myxococcus xanthus using an oligonucleotide probe representing conserved regions of biotin carboxylase subunits of acetyl coenzyme A (acetyl-CoA) carboxylases. The fragment contained two open reading frames (ORF1 and ORF2), designated the accB and accA genes, capable of encoding a 538-amino-acid protein of 58.1 kDa and a 573-amino-acid protein of 61.5 kDa, respectively. The protein (AccA) encoded by the accA gene was strikingly similar to biotin carboxylase subunits of acetyl-CoA and propionyl-CoA carboxylases and of pyruvate carboxylase. The putative motifs for ATP binding, CO(2) fixation, and biotin binding were found in AccA. The accB gene was located upstream of the accA gene, and they formed a two-gene operon. The protein (AccB) encoded by the accB gene showed high degrees of sequence similarity with carboxyltransferase subunits of acetyl-CoA and propionyl-CoA carboxylases and of methylmalonyl-CoA decarboxylase. Carboxybiotin-binding and acyl-CoA-binding domains, which are conserved in several carboxyltransferase subunits of acyl-CoA carboxylases, were found in AccB. An accA disruption mutant showed a reduced growth rate and reduced acetyl-CoA carboxylase activity compared with the wild-type strain. Western blot analysis indicated that the product of the accA gene was a biotinylated protein that was expressed during the exponential growth phase. Based on these results, we propose that this M. xanthus acetyl-CoA carboxylase consists of two subunits, which are encoded by the accB and accA genes, and occupies a position between prokaryotic and eukaryotic acetyl-CoA carboxylases in terms of evolution.